Politik Pembangunan Denpasar Smart City Oleh Walikota Denpasar - Dharmaanggara, Putu Editya; Noak, Piers Andreas; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2021)
This In the current era of globalization, fast, precise , and accuratee information servicess are needed. Pro Denpasar application is the application of thesmartcity concept by utilizing technology and communication to realize better public services. This study tries to describe how the politic of Denpasar Smart City development by the Mayor of Denpasar as a development political actor develops Denpasar Smart City. The theory used to explain the problem is the theory of development politics and the theory of  development political actors. This research uses descriptive research and qualitative research methods, namely by using in-depth interview with relevant government agencies, the community and l literature s tudies to explore the development of Denpasar Smart City and determine d political impact of the developmen t ofthe Mayor of Denpasar on the community.   Keywordss: Denpasar City, Political Development. Smart City.